2009
DOI: 10.1007/s00125-009-1485-6
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell signalling supports pancreatic beta cell function in the rat

Abstract: Aims/hypothesis The proximity of endothelial cells and beta cells in islets by necessity means that they are exposed to each other's products. Whereas islet endothelial cells require signals from beta cells to function properly, endothelin-1, thrombospondin-1 and laminins, among others, have been identified as endothelial-derived molecules, although their full effects on beta cells have not been explored. We tested the hypothesis that islet endothelialderived products affect beta cell function. Methods Endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 34 publications
4
80
2
Order By: Relevance
“…This is in accordance with previous studies demonstrating that the revascularisation of smaller islets after transplantation is more efficient than that of larger islets [37], an effect that is likely to be amplified by the large aggregates formed in our islet-alone grafts. The re-establishment of a blood supply is of obvious importance for the survival and function of the islets, but it is also clear that paracrine interactions between beta cells and endothelial cells are important in maintaining beta cell function [38]. The improved recovery of these interactions in the islet+MSC grafts may account for some beneficial effects of the MSC co-transplant in our model.…”
Section: Discussionmentioning
confidence: 87%
“…This is in accordance with previous studies demonstrating that the revascularisation of smaller islets after transplantation is more efficient than that of larger islets [37], an effect that is likely to be amplified by the large aggregates formed in our islet-alone grafts. The re-establishment of a blood supply is of obvious importance for the survival and function of the islets, but it is also clear that paracrine interactions between beta cells and endothelial cells are important in maintaining beta cell function [38]. The improved recovery of these interactions in the islet+MSC grafts may account for some beneficial effects of the MSC co-transplant in our model.…”
Section: Discussionmentioning
confidence: 87%
“…The normally low oxygenation of transplanted islets may affect islet survival and function, because it means that their metabolism tends to be much more anaerobic than that of endogenous islets and results in lactate formation and tissue acidosis (48). Several recent reports also indicate that endothelial cell signaling may be important for ␤-cell function and growth (19,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The perfusions were concluded by a 15-min perfusion with medium containing 2.8 mmol/l glucose. A 1.0-ml sample was collected at 14,15,16,17,18,19,20,22,25,30,35,40,45,50,55, and 60 min. The insulin concentrations of the effluent samples were measured by ELISA (Mercodia).…”
Section: Methodsmentioning
confidence: 99%
“…In this way, b-cells are exposed to other cell-derived molecules that can affect the physiological regulation of glucose-induced insulin secretion. It was demonstrated that endothelial-derived molecules, like endothelin-1, thrombospondin-1, and laminins, among others, can improve b-cell function [45][46][47]. These data show the importance of soluble factors secreted by islet vicinity, suggesting that the addition of soluble factors can also interfere in cell differentiation.…”
mentioning
confidence: 92%
“…The pancreatic islets in the adult are among the most vascularized of all organs in the body, with a unique dense glomerular-like angioarchitecture [45]. In this way, b-cells are exposed to other cell-derived molecules that can affect the physiological regulation of glucose-induced insulin secretion.…”
mentioning
confidence: 99%